Gelijkgesteld: The Change of Chinese Legal Status Under Indonesian Colonial Structure - Juwono, Harto (Published by Confucius Institute UNS, 2024)
This research attemps to reveal a phenomenon of legal history that has occurred so far, namely the process of achieving equal rights or internal naturalisation of the Chinese ethnic in Indonesia. The time period chosen is the colonial era with the consideration that at the time this ethnicity was directly involved in the legal system. By researching it, it is hoped that it can be known where the actual aim of granting the status of subject and citizen to the Chinese people in the colonial legal system and will continue in the national legal system. Considering that the chosen period is the Dutch East-Indies era, this paper uses historical research method with an emphasis on contemporary archival sources, which are traced, critiqued, analysed, and finally reconstructed. Based on the chosen theme of legal status, the archives that are used mostly take legal history data such as colonial era regulations and testimonies of their applications or public responses in contemporaneous newspapers. As a conclusion, it can be stated that Chinese ethnic were the object of policy and were not negatively responsive but accepted it with the hope of achieving the most benefit from the policy that was applied to them.